2019
DOI: 10.3892/ol.2019.9980
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑1291 mediates cell proliferation and tumorigenesis by downregulating MED1 in prostate cancer

Abstract: miRNAs are important factors involved in the regulation of tumor development. miR-1291 was found to have regulatory effects in many tumors, but its role in prostate cancer (PCa) still remains unclear. We explored the expression of miR-1291 in PCa to reveal its role in regulating the progression of PCa as well as its underlying mechanism. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to detect the expression of miR-1291 in PCa tissues and cell lines compared to normal tissues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Studies showed that miR-1291 had anti-tumor effects in multiple cancers including renal cancer, esophagus cancer, pancreatic cancer, and prostate cancer [34][35][36][37]. As the target for miR-1291, several molecules have been identi ed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies showed that miR-1291 had anti-tumor effects in multiple cancers including renal cancer, esophagus cancer, pancreatic cancer, and prostate cancer [34][35][36][37]. As the target for miR-1291, several molecules have been identi ed.…”
Section: Discussionmentioning
confidence: 99%
“…These include SLC2A1/GLUT1 in A498 and 786-O renal cancer cells [34], MUC1 in human esophagus cancer EC9706 and EC-1 cells [35], the forkhead box protein A2-anterior gradient 2 (FOXA2-AGR2) pathway in PANC-1 pancreatic cancer cells [36]. Furthermore, miR-1291 has been shown to inhibit cell growth and tumorigenesis in prostate cancer by binding to MED1 [37]. However, to the best of our knowledge, there is no previous report of miR-1291 in CRC which is one of the widespread cancers in the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were consistent with a previous study reporting that MED1 was often either upregulated or downregulated in melanoma 36 , which also showed that low MED1 expression correlated with a highly tumorigenic phenotype. Multiple other studies have also demonstrated that MED1 31,[37][38][39][40][41] and Mediator subunits are deregulated in melanoma and other cancer types 31,[42][43][44][45][46] . The observed differences in expression of different MEDs may translate into diffences in the activity of the Mediator complex to support tumorigenesis and specific phenotypes, such as SSX2 expression.…”
Section: Expression Of Mediator Subunits Is Deregulated In Melanomamentioning
confidence: 90%
“…In recent years, miR-1291 has been demonstrated to have anti-tumor effects in carcinoma of the kidney, esophagus, pancreas, and prostate [31][32][33][34]. However, to the best of our knowledge, miR-1291 in CRC has not been reported.…”
Section: Introductionmentioning
confidence: 90%